CAPACITY OF INDONESIAN FOREST AS CO2 SINK: COMPARING AN INTACT PRIMARY FOREST OF LORE LINDU NATIONAL PARK CENTRAL SULAWESI WITH DEGRADED AND DRAINED PEATLAND FOREST IN CENTRAL KALIMANTAN - Tania June (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
This article compares the capacity of undisturbed tropical forest in absorbing COand acts as a net sink with the disturbed (drained) peatland forest acting as a net source. Undisturbed forest of Lore Lindu National Park (LLNP) absorbs substantial amount of CO22 with low ecosystem respiration resulted in a net absorbtion reaching -970 gCm-2 year-1. Data from a disturbed peatland forest in Central Kalimantan shows that although absorption was higher than the LLNP area ecosystem respiration of this drained peatland resulted in a big net emission reaching 447 gCm-2 year-1. Recovery of the hydrological system of the area, reduced emission substantially.This article compares the capacity of undisturbed tropical forest in absorbing COand acts as a net sink with the disturbed (drained) peatland forest acting as a net source. Undisturbed forest of Lore Lindu National Park (LLNP) absorbs substantial amount of CO22 with low ecosystem respiration resulted in a net absorbtion reaching -970 gCm-2 year-1. Data from a disturbed peatland forest in Central Kalimantan shows that although absorption was higher than the LLNP area ecosystem respiration of this drained peatland resulted in a big net emission reaching 447 gCm-2 year-1. Recovery of the hydrological system of the area, reduced emission substantially.